(untitled) (Educational Dimension, 2024)
Cyberbullying has become one of the misconducts among the youth due to an increased use of the internet in the educational context. The bibliometric analysis was carried out to determine the global trends in the evolution of cyberbullying among the youth in higher learning institutions (HLIs). The analysis involved 1073 research articles published between 2008 and 2022 retrieved from the Dimensions scientific database. The VOSviewer 1.6.20 software was used to establish visualisation networks. The results indicate a rapid growth of research articles on cyberbullying from 2019 to 2022, where most HLIs migrated to virtual teaching due to the outbreak of COVID-19. The developed countries had high rates of research publications and strong collaboration patterns in cyberbullying. The results also indicate factors such as harsh parenting and moral disengagement to be the causes of cyberbullying. The analysis shows that publications on cyberbullying from developing countries are very low compared with their developed counterparts. Examining the trends in cyberbullying among youth in HLIs offers new insights into the prevalence, forms, and concerns of cyberbullying within this specific population of HLIs. This study enhances our understanding of cyberbullying consequences and broadens our knowledge about how increased autonomy among youth in using technology immorally can fasten the growth of cyberbullying in HLIs. This study informs the development of appropriate intervention strategies within HLIs that promote digital safety and citizenship. HLIs can also utilise the findings to develop rules and regulations that address cyberbullying within their institutions. Conducting a systematic review of the effective prevention and intervention strategies on cyberbullying employed by HLIs in different contexts may provide more insights into shaping youth in promoting digital safety.